Using social and information technologies for disaster and crisis management - Jennex, Murray E. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book highlights examples of disaster situations in recent years in which social and information technologies were useful in distributing and receiving information updates"--Provided by publisher.
Includes bibliographical references
Restricted to subscribers or individual electronic text purchasers